Power management unit for low power wireless sensor network - Puah, Yin Soon (2022)
Wireless sensor networks play an important role in monitoring the condition of the railway structure in the railway transport industry. However, a commercial wireless sensor node is not very promising for this application since the batteries will degrade over a certain time. Moreover, these wireless sensors that were used to monitor the condition of railways were usually deployed in harsh environments such as rural railways, hence making the battery changing process harder. The importance of this study is to provide an infinite power source for the wireless sensor nodes in railway monitoring applications by designing a power management unit (PMU) that manages the harvested power effectively. The available ambient energies were studied and an electromagnetic kinetic energy harvester was chosen and modelled. The PMU is targeted to regulate the harvested energies from the passing trains (harvested by a Electromagnetic Kinetic Energy Harvester) and outputs a stable 3.3 V to the loads. The PMU proposed in this study includes a rectifier and buck converter and it was constructed in 45nm CMOS technology. The performance of the PMU proposed has been analysed and proven to achieve an efficiency of more than 80% and a power of 36 mW was successfully generated which is sufficient to power the wireless sensor. This approach results in low power consumption, low output current and voltage ripple.